2018
DOI: 10.1111/jvp.12715
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and physiologic/behavioral effects of buprenorphine administered sublingually and intravenously to neonatal foals

Abstract: Buprenorphine is absorbed following sublingual administration, which would be a low‐stress delivery route in foals. However, the pharmacokinetics/pharmacodynamics are not described in foals. Six healthy foals <21 days of age participated in a blinded, randomized, 3‐period, 5‐sequence, 3‐treatment crossover prospective study. Foals received 0.01–0.02 mg/kg buprenorphine administered SL or IV with an equivalent volume of saline administered by the opposite route. Blood was collected from the cephalic vein for ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…The primary metabolite of buprenorphine is norbuprenorphine, which was undetectable following transdermal administration in the study. This analysis was in accordance with previous studies where norbuprenorphine was unmeasurable following either intravenous or sublingual route ( 38 , 40 , 42 ). Considering norbuprenorphine has only 25% of the intrinsic analgesic activity of buprenorphine and a low permeability into the brain, it may have minimal clinical significance ( 45 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The primary metabolite of buprenorphine is norbuprenorphine, which was undetectable following transdermal administration in the study. This analysis was in accordance with previous studies where norbuprenorphine was unmeasurable following either intravenous or sublingual route ( 38 , 40 , 42 ). Considering norbuprenorphine has only 25% of the intrinsic analgesic activity of buprenorphine and a low permeability into the brain, it may have minimal clinical significance ( 45 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous exploratory studies with buprenorphine in horses utilized average doses of 5–10 µg/kg via intravenous ( 18 , 20 , 21 , 33 41 ), intramuscular ( 23 , 24 , 38 , 42 ) and sub-lingual ( 40 , 42 , 43 ) routes. A common observation in most of these studies irrespective of the route used was its potential for inducing excitement, increasing spontaneous locomotory activity, decreasing gut sounds and elevating HR in healthy pain-free horses.…”
Section: Discussionmentioning
confidence: 99%
“…Bioavailability of buprenorphine from the sublingual route has been investigated in two studies; one study documented good absorption when plasma concentrations were measured in samples from the jugular vein, but the study also demonstrated a significantly higher concentration in blood obtained from the jugular vein than blood obtained from the lateral thoracic vein, although pharmacokinetics were not determined from these samples . A second study, in foals, demonstrated only 25% bioavailability when plasma concentrations were measured in samples taken from the cephalic vein and the sublingual dose tested (0.02 mg/kg) failed to achieve plasma concentrations associated with analgesia in experimental models . The dose used in the case report described above was one‐third of this dose (0.006 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…Previous exploratory studies with buprenorphine in horses utilized average doses of 5–10 µg/kg via intravenous ( 18 , 20 , 21 , 40 , 42 48 ), intramuscular ( 23 , 24 , 39 , 49 ), and sublingual ( 40 , 42 , 50 ) routes. A common observation in most of these studies irrespective of the route used was its potential for inducing excitement, increasing spontaneous locomotory activity, decreasing gut sounds, and elevating HR in healthy pain-free horses.…”
Section: Discussionmentioning
confidence: 99%